Basic Physicochemical Properties of Polyethylene Glycol Coated Gold Nanoparticles that Determine Their Interaction with Cells. (29th March 2016) - del Pino, Pablo; Yang, Fang; Pelaz, Beatriz; Zhang, Qian; Kantner, Karsten; Hartmann, Raimo; Martinez de Baroja, Natalia; Gallego, Marta; Möller, Marco; Manshian, Bella B.; Soenen, Stefaan J.; Riedel, René; et al.
Abstract: A homologous nanoparticle library was synthesized in which gold nanoparticles were coated with polyethylene glycol, whereby the diameter of the gold cores, as well as the thickness of the shell of polyethylene glycol, was varied. Basic physicochemical parameters of this two‐dimensional nanoparticle library, such as size, ζ‐potential, hydrophilicity, elasticity, and catalytic activity, were determined. Cell uptake of selected nanoparticles with equal size yet varying thickness of the polymer shell and their effect on basic structural and functional cell parameters was determined. Data indicates that thinner, more hydrophilic coatings, combined with the partial functionalization with quaternary ammonium cations, result in a more efficient uptake, which relates to significant effects on structural and functional cell parameters. Abstract : Eine homologe Bibliothek von Polyethylenglycol‐überzogenen Goldnanopartikeln mit variierender Dicke von Kern und Schale wurde hergestellt, und physikochemische Parameter der Nanopartikel wurden bestimmt. Die Aufnahme ausgewählter Nanopartikel durch Zellen und ihr Einfluss auf deren strukturelle und funktionelle Parameter wurden untersucht.